Development of integrative Islamic personality model - Tekke, Mustafa; Ismail, Nik Ahmad Hisham (İnsan ve Toplum Bilimleri Araştırmaları Dergisi, 2016)
Personality in Islam is understood as an all encompassing way of life, resulting in an approach that is able to connect every aspect of behavior, attitude, and feeling for Muslims. The existing gap in instrumentation capable of capturing the major elements of the Islamic personality can only be filled by beginning with an organic definition and concept for personality from the Islamic perspective. This study presents reconceptualization of personality in religion as an Integrative Islamic Personality Model (IIPM) developed by using the ideas of Carl Rogers and Said Nursi. This model comprised of four constructs; Belief in God, Awareness of Prophetic Teaching, Self-striving and Self-regard. This personality measurement within Islamic and Western perspectives is greatly considered to be beneficial to educators and counselors in order to measure relevant personality of an individual.